INCREASING THE EFFICIENCY OF FOREIGN LANGUAGE TEACHING BASED ON A PERSONALIZED APPROACH - Doston Sherov (Bright Mind Publishing, 2025)
The effectiveness of foreign language education largely depends on the teaching approaches used in the learning process. In recent years, the student-centered approach has gained increasing attention as a method to enhance language acquisition by prioritizing individual learning needs, preferences, and motivations. This study explores the impact of a student-centered approach on improving the effectiveness of foreign language education, particularly in the context of English language learning in Uzbekistan. The research examines key principles of this approach, including active participation, personalized learning paths, and the integration of real-life communication tasks. By analyzing various didactic strategies, technological tools, and assessment methods, the study aims to determine how student-centered learning fosters language proficiency, engagement, and motivation among students. The findings suggest that adopting a student-centered methodology leads to greater autonomy, improved speaking and writing skills, and higher retention rates. The study concludes with recommendations for implementing student-centered teaching methods in higher education institutions to enhance foreign language education effectiveness.
Keywords: Student-centered learning, foreign language education, active learning, personalized instruction, communicative competence, motivation, learner autonomy, higher education.